Energy efficiency and heating technology investments: Manipulating financial information in a discrete choice experiment - Ghislaine Lang; Mehdi Farsi; Bruno Lanz; Sylvain Weber (University of Neuchâtel, Institute of Economic Research (IRENE), 2021)
We elicit homeowners' willingness to pay (WTP) for energy efficiency and low-carbon technologies in the context of heating appliance replacement. We employ a within-between subject design that involves manipulating information in a two-stage discrete choice experiment (DCE) and use WTP space estimation to identify the role of financial information in reducing fossil fuel use. We find that homeowners' average valuation of energy efficiency exceeds associated heating cost savings, suggesting that they also consider non-monetary benefits when evaluating this type of investment, whereas information about private and pro-social benefits of investments only has a limited impact on WTP. Evidence also suggests that homeowners have a strong preference for the pre-existing technology. Consequently, fossil fuel users' WTP for switching to low-carbon technologies does not cover respective investment cost differentials, and we derive evidence on how combined subsidies and information can incentivize these users to opt out of fossil technologies.
Keywords: D1; D8; H23; Q4; Q5; R31; 330; Energy efficiency; Low-carbon technologies; Informational interventions; Product familiarity; Discrete choice experiments; Mixed logit models; WTP space estimation